1983
DOI: 10.1901/jeab.1983.40-69
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Derived Stimulus Relations Through Training in Arbitrary‐matching Sequences

Abstract: Five‐year‐old children were taught three‐stage sequences of arbitrary matching: A‐C, B‐C, A‐D; A‐C, B‐D, B‐C; or A‐C, A‐D, B‐C. Each stage refers to a sample‐comparison relation between stimuli. Unreinforced test probes revealed untrained arbitrary matches (B‐D, A‐D, and B‐D, respectively), derivable by substitution of stimuli with a common sample or comparison function. Additional probes revealed further untrained sample‐comparison relations derivable by substitution and identity, including the commuted relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 5 publications
2
33
1
Order By: Relevance
“…These findings extend the work by PerezGonzalez (1994) and Perez-Gonzalez and Serna (1993) on transfer of compound control with (pre)adolescents and adults, and on functional equivalence of unitary stimuli with young children and animals (e.g. , Astley & Wasserman, 1999;Peterson, 1984;Smeets et aI., 1997Smeets et aI., , 2001Spradlin, Cotter, & Baxley, 1973;Urcuioli & Zentall, 1993;Wasserman et aI., 1992;Wetherby, Karlan, & Spradlin, 1983).…”
Section: Resultssupporting
confidence: 84%
“…These findings extend the work by PerezGonzalez (1994) and Perez-Gonzalez and Serna (1993) on transfer of compound control with (pre)adolescents and adults, and on functional equivalence of unitary stimuli with young children and animals (e.g. , Astley & Wasserman, 1999;Peterson, 1984;Smeets et aI., 1997Smeets et aI., , 2001Spradlin, Cotter, & Baxley, 1973;Urcuioli & Zentall, 1993;Wasserman et aI., 1992;Wetherby, Karlan, & Spradlin, 1983).…”
Section: Resultssupporting
confidence: 84%
“…Stimulus equivalence is not found in retarded children with no spontaneous productive speech, but it is found in normal and retarded children with speech who are matched to the speech-disabled children according to mental age (Devany, Hayes, & Nelson, in press). It is also well known that it is relatively easy to demonstrate stimulus equivalence with humans (e.g., Spradlin, 1983), but it is extremely difficult (indeed it has not yet conclusively been shown) with infrahumans, including the higher primates . Although there is considerable evidence that infrahumans can respond to nonarbitrary relationships based on nonarbitrary aspects of stimuli (e.g., "larger than"; see Reese, 1968), there is little evidence as yet that they can respond on the basis of arbitrary relationships among arbitrary stimuli.…”
Section: Rule-governed Behaviormentioning
confidence: 99%
“…The purposes of this study were therefore twofold: first, to determine whether stimulus classes could be established and progressively enlarged in the absence of dictated names as class members; and second, to ascertain whether subjects who demonstrated equivalences would supply their own mediating labels. Spradlin et al (1973), Stromer and Osborne (1982), and Wetherby, Karlan, and Spradlin (1983) have previously shown that subjects could demonstrate purely visual classes. Our research sought to extend these earlier findings by establishing the conditions for larger classes, determining the role of naming, and testing all the requisite, intermediate equivalences.…”
mentioning
confidence: 95%